Cost Benefit Evaluation and Development Planning For Potential Jetty Facilities in Coal Mining Operation - Olo Angelia Simarmata, Bunga (Journal Research of Social Science, Economics, and Management, 2026)
Indonesia’s coal mining industry remains strategically important for domestic energy security and export competitiveness, making logistics infrastructure a critical determinant of operational performance. As coal production increases due to collaboration with neighboring mines, jetty facilities become potential bottlenecks affecting throughput, cost efficiency, and delivery reliability. This study evaluates the operational and financial performance of three jetty facilities operated by PT XYZ in East Kalimantan to identify the most economically beneficial jetty and assess the feasibility of infrastructure development. The analysis applies an operational cost–benefit approach using operational cash inflows and operating expenditures (OPEX), complemented by operational efficiency indicators such as gross profit margin and net profit margin. Based on comparative results, a Discounted Cash Flow (DCF) analysis is conducted for the selected jetty to evaluate a proposed conveyor development project using Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period. The findings reveal significant differences in cash-generating capability and operational efficiency among the three jetties, with one facility demonstrating superior economic contribution and stronger financial performance. The DCF results indicate that the proposed conveyor development is financially feasible and capable of improving long-term operational capacity. This study provides a cash-based, facility-level evaluation framework that supports data-driven investment decision-making for jetty development in coal logistics operations.